The crisis and national labour law reforms: a mapping exercise - Clauwaert, Stefan; Schömann, Isabelle (Brussels, 2012)
"This Working Paper maps the labour law reforms in various European countries either triggered by the crisis or introduced using the crisis – falsely – as an excuse. Such reforms generally render existing labour law provisions more flexible and loosen minimum standards, shifting the emphasis to soft law (deregulation). The authors critically address this large-scale deregulation of labour law currently taking place, in particular the lack of democratic foundations underlying the reforms and their negative impact on fundamental social rights and workers’ protection. "